If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3(y + -2) = 2x + 21 Reorder the terms: 5x + -3(-2 + y) = 2x + 21 5x + (-2 * -3 + y * -3) = 2x + 21 5x + (6 + -3y) = 2x + 21 Reorder the terms: 6 + 5x + -3y = 2x + 21 Reorder the terms: 6 + 5x + -3y = 21 + 2x Solving 6 + 5x + -3y = 21 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + 5x + -2x + -3y = 21 + 2x + -2x Combine like terms: 5x + -2x = 3x 6 + 3x + -3y = 21 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + 3x + -3y = 21 + 0 6 + 3x + -3y = 21 Add '-6' to each side of the equation. 6 + 3x + -6 + -3y = 21 + -6 Reorder the terms: 6 + -6 + 3x + -3y = 21 + -6 Combine like terms: 6 + -6 = 0 0 + 3x + -3y = 21 + -6 3x + -3y = 21 + -6 Combine like terms: 21 + -6 = 15 3x + -3y = 15 Add '3y' to each side of the equation. 3x + -3y + 3y = 15 + 3y Combine like terms: -3y + 3y = 0 3x + 0 = 15 + 3y 3x = 15 + 3y Divide each side by '3'. x = 5 + y Simplifying x = 5 + y
| x+.14x=1234.62 | | 28=-2(3x-5) | | 70=7000/12*r | | 37+63= | | f(x+9)=x^2+2x+3 | | 4x^1/3-9x^1/3 | | 6x(3+4)=(6+3)+4 | | 3(12-x)=16-2 | | 15=4a | | p-2(3-2p)=2p+9 | | 3y-7x=28 | | x+(x+1.2)+(x-1.2)=28.5 | | (2x-4)*2=26 | | 75=5000/12*r | | p-18=59 | | 6a+18=6 | | 8.5+6*h/2=241.18 | | 99x+10=189 | | 1750-140= | | 3[(5x+3)-4]=4(2x-3) | | ln(x^2+3x)=2ln(2) | | 2a+18=6 | | 3[(5zx+3)-4]=4(2x-3) | | 5s-2+3(s-4)=5 | | .6c+11=2c+59 | | -6=-4(x+3)+2x | | -3(6p+2)-2(3-14p)=3(4+3p) | | 2(n+9)=5n | | -9/8t=7/10 | | -2p-(-10)+7p=-5 | | c+150=1750 | | -3b-4-3=5 |